AB0481 Abatacept Might not Alter Anti-Cyclic Citrullinated Peptide Levels in Established Rheumatoid Arthritis Patients -Airtight Study-. (9th June 2015) - Anno, S.; Inui, K.; Mamoto, K.; Okano, T.; Sugioka, Y.; Tada, M.; Koike, T.; Nakamura, H.
Abstract : Background: The percentage of anti-cyclic citrullinated peptide (CCP)-positive patients reported declines among early rheumatoid arthritis (RA) patients treated with abatacept (ABT). Objectives: The AIRTIGHT study (UMIN:000005570) was conducted to assess the clinical and immunological impact of ABT on established RA patients. Methods: The AIRTIGHT study included 32 patients (mean age, 60.7±13.6 years; mean duration of disease, 11.7±13.6 years; range, 0-35 years; MTX use, 81.9%; mean MTX dose, 6.1±4.6 mg/week) treated with ABT and 72 patients (mean age, 59.7±14.3 years; mean duration of disease, 9.5±10.9 years; range, 0-40 years; MTX use, 86.1%; mean MTX dose, 8.6±4.3 mg/week) treated with non-ABT biologics (adalimumab, n=20; etanercept, n=14; tocilizumab, n=19; infliximab, n=10; golimumab, n=9). Serum levels of anti-CCP, rheumatoid factor (RF), and autoantibody to galactose-deficient immunoglobulin (Ig)G (CA-RF) were measured at baseline and 48 weeks after treatment. Paired t-tests were used to compare changes in anti-CCP, RF, and CA-RF between each time point. Results: Mean DAS28 score decreased from 4.5±1.3 to 3.5±1.3 after 48 weeks on ABT. Titers of anti-CCP were 143.4±176.0 U/ml at baseline and 151.1±176.1 after 48 weeks of treatment, values for RF were 150.4±233.7 IU/ml at baseline and 137.0±191.0 IU/ml after 48 weeks of treatment, and values of CA-RF were 163.0±301.4 AU/ml at baseline and 152.8±249.3 after 48 weeks of treatment on ABT. Titers of anti-CCP (p=0.64), RF (p=0.63) and CA-RF (p=0.57) were unchanged during ABT treatment. Seven patients who achieved improvement (good DAS28 response) on ABT also did not show the decraese of those titers. Titers of anti-CCP (p=0.47), RF (p=0.12) and CA-RF (p=0.12) did not correlate significantly with changes in DAS28. Mean DAS28 decreased from 4.5±1.3 to 2.8±1.1 at 48 weeks on non-ABT. Titers of anti-CCP were 147.1±145.9 U/ml at baseline and 109.7±138.8 IU/ml after 48 weeks of treatment, levels of RF were 145.5±201.3 IU/ml at baseline and 75.4±106.0 IU/ml after 48 weeks of treatment, and levels of CA-RF were 170.1±280.7 AU/ml at baseline and 95.3±130.1 AU/ml after 48 weeks of treatment with non-ABT. Titers of anti-CCP (p<0.001), RF (p<0.001) and CA-RF (p=0.002) were reduced significantly during non-ABT treatment. Conclusions: These findings suggest that the titer of autoimmunity did not decrease during ABT treatment in established RA, regardless of disease activity. Although the titer of autoimmunity decreases during non-ABT treatment in established RA, percentage of MTX use might be involved (ABT: 71.9%, non-ABT: 86.1%; p=0.05). Disclosure of Interest: None declared